Analysis of volatiles in Dezhou Braised Chicken by comprehensive two-dimensional gas chromatography/high resolution-time of flight mass spectrometry. Issue 2 (March 2015) - Duan, Yan; Zheng, Fuping; Chen, Haitao; Huang, Mingquan; Xie, Jianchun; Chen, Feng; Sun, Baoguo
Abstract: A fast and mild extraction method and an accurate identification method to analyze the volatiles in non-volatile food matrices were set up. The accelerated solvent extraction followed by solvent assisted flavor evaporation (ASE-SAFE) was used to extract the volatiles from Dezhou braised chicken. The extract was analyzed by a comprehensive two-dimensional gas chromatography/high resolution-time of flight mass spectrometry (GC × GC/HR-TOFMS) and a GC-qMS. Ninety one compounds were identified by GC × GC/HR-TOFMS with an aid of the NIST08 library and accurate mass determination, 44 compounds were identified by GC-qMS only with the NIST08 library. The main odor-active constitutes of the Dezhou braised chicken were carbonyl compounds (33.04%). 2-Enals and 2, 4-dineals were considered to be the most important odor-active constitutes in chicken. In our study, 6 very polar and unstable 2-enals or 2, 4-dineals compounds, including ( E )-2-hexenal, ( E )-2-nonenal, ( Z )-2-decenal, ( E )-2-undecenal, ( E, E )-2, 4-heptadienal and ( E, E )-2, 4-nonadienal, were only identified by GC × GC/HR-TOFMS. Three very polar and unstable furanones, including 5-acetyldihydro-2(3 H )-furanone (0.04%), dihydro-3-hydroxy-4, 4-dimethyl-2(3 H )-furanone (0.32%) and 2, 5-dimethyl-4-hydroxy-3(2 H )-furanone (0.32%) were also only detected by the GC × GC/HR-TOFMS. Some trace sulfur-containing and nitrogen-containing compounds, including disulfide dipropyl (0.05%), 2-acetylthiazole (0.06%), 2-pyrrolidinone (0.15%) and benzothiazole (0.07%) that might play important roles in the flavor of chicken, were also only found by the GC × GC/HR-TOFMS. Highlights: A fast and effective extraction method (ASE-SAFE) is set up. An accurate identification method (GC × GC/HR-TOFMS) is set up. Some very polar and unstable odor-active and trace constitutes can be qualified. 6 Compounds of 2-enals or 2, 4-dineals are only identified by GC × GC/HR-TOFMS. The problem of overlapped peaks in TIC of GC-MS is resolved by GC × GC/HR-TOFMS.